Small Area Estimation For Mapping Human Development Index - Moh. Yamin Darsyah; Rochdi Wasono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract.Human Development Index (HDI) is one ofthe indicators that used to determine the human developmentofa country. The calculation of the value of HDI in Indonesia is carried out until the scale of the districteach year. Since the implementation of regional autonomy policy,the calculation of the HDI value is required with a smaller scale in the district. The calculation of HDI values with sub-scale is difficult because the sample is toosmall to estimate the value of HDI perdistrict. One of the component stocalculate the value of HDI is an indexof purchasing power that approximated by the value of percapita expenditure. Small Area Estimation is one of the indirect estimates that used to estimate the parameter values of the subpopulation. On this research, Small Area Estimation (SAE) is a statistics methode for estimate small sampel .The research purpose to estimate per capita expenditurefor HDI in Demak District. The results of the estimation with SAE methods in Demak District indicates that the Demak Sub-district has the largest per capita expenditure that can be said have the highest HDI value while Kebonagung Sub-district has the smallest per capita expenditure that can be said have the lowest HDI value.